Comparing the clinical success rate of the dorsolateral approach to the medial approach for injection of the centrodistal joint in the horse. (28th March 2019) - Hoaglund, E. L.; Seabaugh, K. A.; Selberg, K. T.; Hess, A.; Bass, L.
Summary: Background: Centrodistal joint injection is an important component of lameness evaluation and treatment. Successful injection is poor for the medial approach. The dorsolateral approach is an alternative but has not been validated with contrast medium. Radiograph‐guidance has not been studied to determine its necessity or benefit for either approach. Objectives: To determine if the dorsolateral approach to the centrodistal joint is more successful than the medial approach. To determine if radiograph‐guidance is beneficial. Study design: Prospective, randomised study. Methods: Three operators injected 98 centrodistal joints in total, each horse served as its own control. In Phase 1, injections were performed by standard technique. In the Phase 2, operators were allowed to use radiography to assist needle placement. Contrast deposition was evaluated by a single radiologist. Results: Without radiographic assistance, 10/25 (40%) joints were successfully injected using either the medial or dorsolateral approach. With radiographic assistance, 19/24 (79%) joints were successfully injected using the medial approach, 11/24 (46%) joints were successfully injected using the dorsolateral approach. Main limitations: The population consisted of aged horses representing a variety of breeds with existing osteoarthritis, and multiple operators were recruited. Conclusions: The dorsolateral approach was equivalent to the medial approach when traditional injection techniques were used. Radiograph‐guidance improved success of the medial approach, but not the dorsolateral approach. Many injections performed from the dorsolateral approach (32/49; 65%) resulted in extensive perivascular subcutaneous contrast deposition after infiltration into the tarsal canal. Further research is needed to improve injection success of the centrodistal joint when using the dorsolateral approach.